BORATING OF CARBON AND ALLOY STEEL IN BOILING LAYER - N. G. Koukhareva; S. N. Petrovich; N. A. Galynskaya; V. F. Protasevich; T. F. Smirnova (Наука и техника)
The paper describes how to obtain boride coatings on steel 20, 4X5MФС, X12M being treated in a boiling layer of metallothermic powder environment. Phase and chemical compositions, hardness and wear- resistance of boride coatings